Evaluation of Deep Gray Matter by Diffusion-WeightedImaging in Children with Tuberous Sclerosis Complex - Eroğlu, Yeşim; Koc, Mustafa (My University, 2021)
Objective: The aim of this study is to compare diffusion-weighted magnetic resonance imagingvalues of deep gray matter structures in children diagnosed with tuberous sclerosis complex with acontrol group.Materials and Methods: Between January 2015 and December 2020, 14 pediatric patients (8boys, 6 girls; mean age 9.50±4.16) diagnosed with tuberous sclerosis complex who underwentdiffusion-weighted magnetic resonance imaging, and 28 age and sex-matched control patientswere retrospectively analyzed. Apparent diffusion coefficient values were measured by placingsymmetric circular region of interest on bilateral thalamus and basal ganglia. Results: A significant increase was found in the apparent diffusion coefficient values in the bilateralnucleus caudate compared to the control group in patients diagnosed with tuberous sclerosiscomplex (P<0.001). Conclusion: Affecting possible deep gray matter structures in these patients may explain thephysiopathology for current clinical findings and neurological disorders that may develop.
Keywords: Nörolojik Bilimler; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme; Pediatri